An Econometric Analysis of the European Commission's Merger Decisions - Mats A. Bergman; Maria Jakobsson; Carlos Razo (Uppsala University, Department of Economics, 2003)
Using a sample of 96 mergers notified to the EU Commission and logit regression techniques, we analyse the Commission's decision process. We find that the probability of a phase 2 investigation and of a prohibition of the merger increases with the parties' market shares. The probability increases also when the Commission finds high entry barriers or that post-merger collusion is easy. We do not find significant effects of political variables, such as the nationality of the merging firms or the identity of the commissioner.
urn:nbn:se:uu:diva-4460
Keywords: D78; K31; L40; 330; competition law; antitrust; merger; merger reulation; Wettbewerbsrecht; Kartellrecht; Fusionskontrolle; EU-Staaten